The scaling of fine root nitrogen versus phosphorus in terrestrial plants: A global synthesis. (24th August 2019) - Wang, Zhiqiang; Yu, Kailiang; Lv, Shiqi; Niklas, Karl J.; Mipam, Tserang Donko; Crowther, Thomas W.; Umaña, María N.; Zhao, Qi; Huang, Heng; Reich, Peter B.
Abstract: Leaves and roots may differ in nitrogen (N), phosphorus (P) and N:P stoichiometry, which can influence plant growth and ecosystem functioning. As compared to leaves, however, relatively little is known about the N versus P scaling relationship and N:P stoichiometry in root systems, particularly in fine roots. We used a global dataset comprising 1, 890 observations for a total of 763 terrestrial plant species in 123 families (spanning 433 sites world‐wide) to examine live fine root N and P concentrations and stoichiometry, and to determine the scaling of N versus P within and across different plant groups and ecosystems. The global geometric mean values of fine root N and P concentrations and N:P ratios were 10.84 mg/g, 0.94 mg/g and 11.55, respectively. Fine root N and P concentrations and N:P ratios varied both within and across plant groups and ecosystems. A 0.82‐power law described the scaling of fine root N with respect to P across the entire dataset and for major plant phylogenetic and functional groups; however, the numerical value of the N versus P scaling exponent declined from the tropics to higher latitudes and varied significantly at different local sites. Soil nutrient account for much of the variation observed in the scaling of fine root N versus P concentration at different local sites. This study advances our knowledge about limiting resource allocation strategies in below‐ground organs and has important implications for modelling plant growth at local, regional and global levels. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.